If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3y + -5)(8 + -1y) = 0 Reorder the terms: (-5 + 3y)(8 + -1y) = 0 Multiply (-5 + 3y) * (8 + -1y) (-5(8 + -1y) + 3y * (8 + -1y)) = 0 ((8 * -5 + -1y * -5) + 3y * (8 + -1y)) = 0 ((-40 + 5y) + 3y * (8 + -1y)) = 0 (-40 + 5y + (8 * 3y + -1y * 3y)) = 0 (-40 + 5y + (24y + -3y2)) = 0 Combine like terms: 5y + 24y = 29y (-40 + 29y + -3y2) = 0 Solving -40 + 29y + -3y2 = 0 Solving for variable 'y'. Factor a trinomial. (-8 + y)(5 + -3y) = 0Subproblem 1
Set the factor '(-8 + y)' equal to zero and attempt to solve: Simplifying -8 + y = 0 Solving -8 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + y = 0 + 8 y = 0 + 8 Combine like terms: 0 + 8 = 8 y = 8 Simplifying y = 8Subproblem 2
Set the factor '(5 + -3y)' equal to zero and attempt to solve: Simplifying 5 + -3y = 0 Solving 5 + -3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3y = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3y = 0 + -5 -3y = 0 + -5 Combine like terms: 0 + -5 = -5 -3y = -5 Divide each side by '-3'. y = 1.666666667 Simplifying y = 1.666666667Solution
y = {8, 1.666666667}
| 4(x)=3x-1 | | X^2+x=0.24 | | 3(1)-2(6)=9 | | 5x+1=-16 | | 6(y+2)=-3(6y-1)+6y | | 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 | | -x(0)+5y=15 | | -x+0=15 | | 2y-42=4 | | a+4-a(a+4)=0 | | 5h+24=-8(b-6)+6b | | sin(x)=0.5625 | | 1a-4b+2c=0 | | 8p=9 | | 2+19=43 | | sinx=0.5625 | | x(x-8)+2(x-8)=0 | | 5+3y=9 | | Y=5x^2+35 | | z-34.7=68.2 | | 10x+8y+z=100 | | 6x-30=6x+12 | | 5ln(x^2)=4ln(x^3)+6 | | 3x^2-11=37 | | Cry+z=9fory | | y(y-12)+y-12=0 | | 12X+2=76 | | 12X+2=78 | | -4(2x-6)=-6 |